Nano-laminated thin film metallic glass design for outstanding mechanical properties. (October 2018) - Kontis, P.; Köhler, M.; Evertz, S.; Chen, Y.-T.; Schnabel, V.; Soler, R.; Bednarick, J.; Kirchlechner, C.; Dehm, G.; Raabe, D.; Schneider, J.M.; Gault, B.
Abstract: We report the enhancement of fracture toughness and strength of a cobalt‑tantalum-based metallic glass thin film with increasing boron content. The improvement of the mechanical performance is attributed to the formation of a compositionally lamellar compared to uniform glass microstructure, which becomes thinner with increasing boron content as revealed by transmission electron microscopy. Compositional variations across the lamellar structure are revealed by atom probe tomography. Cobalt- and boron-rich regions alternate sequentially, whereas tantalum exhibits slight variations across the lamellae. Our results can be utilized in future design efforts for metallic glass thin films with outstanding mechanical performance. Graphical abstract: Unlabelled Image